(untitled) (Texas Journal of Philology, Culture and History, 2025)
The article is dedicated to the linguistic and cultural analysis of phraseological units in Russian and English. Phraseologisms, as an important part of the lexicon, not only reflect linguistic norms but also carry cultural peculiarities, worldview, and traditions of the people. The article examines both similarities and differences in phraseological expressions between the two languages, focusing on cultural realities, animal images, nature, labor activities, and social stereotypes. The linguistic-cultural approach helps uncover the deep connections between language and culture, revealing the unique features of how the world is perceived by speakers of different languages.